The Impact of 5-HT(3)RA Use on Cost and Utilization in Patients with Chemotherapy-Induced Nausea and Vomiting: Systematic Review of the Literature - Broder, Michael S. (Engage Healthcare Communications, LLC, 2014)
BACKGROUND: Individual studies have assessed the impact of standard prophylactic therapy with 5-hydroxytryptamine receptor antagonists (5-HT(3)RAs) for chemotherapy-induced nausea and vomiting (CINV) on cost and utilization, but no synthesis of the findings exists. OBJECTIVE: To systematically review published literature on costs and utilization associated with CINV prophylaxis with palonosetron and other 5-HT(3)RAs. METHODS: PubMed and the National Institute for Health Research Centre for Reviews and Dissemination databases, conferences of 4 organizations (ie, Academy of Managed Care Pharmacy, American Society of Clinical Oncology, International Society for Pharmacoeconomics and Outcomes Research, and Multinational Association of Supportive Care in Cancer), and the bibliographies of relevant articles were queried for the medical subject headings and key terms of “ondansetron,” “granisetron,” “palonosetron,” “dolasetron mesylate,” “costs,” “cost analysis,” and “economics.” We included records published (full-length articles after 1997 and conference presentations after 2010) in English and with human patients, reporting data on cost and utilization (rescue medication, outpatient and inpatient services) associated with the use of 5-HT(3)RAs for the treatment or prevention of CINV. RESULTS: Of the 434 identified studies, 32 are included in the current analysis: 7 studies report costs, 18 report utilization, and 7 studies report both. The costs are reported in US dollars (7 studies), in Euros (5 studies), and in Canadian dollars (2 studies). The studies vary in designs, patients, 5-HT(3)RA regimens, and the definition of outcomes. The US studies report higher drug costs for CINV prophylaxis with palonosetron compared with ondansetron, lower medical outpatient and inpatient costs for palonosetron versus other 5-HT(3)RAs, and higher acquisition costs for palonosetron versus ondansetron or other 5-HT(3)RAs. Fewer patients receiving palonosetron versus with ondansetron or other 5-HT(3)RAs required rescue medication or used outpatient or inpatient care. In Europe and in Canada, the total pharmacy costs and use of rescue medications reported are lower for patients receiving prophylaxis with palonosetron. CONCLUSIONS: This analysis shows that prophylaxis with palonosetron for the treatment of CINV is associated with higher acquisition treatment costs, but also with lower use of rescue medications and outpatient and inpatient services compared with ondansetron or other 5-HT(3)RAs in the United States. Therefore, the use of palonosetron as a standard treatment may lead to reduced service utilization for CINV.